Medical ethics - Aji Markose; Ramesh Krishnan; Maya Ramesh (Wolters Kluwer Medknow Publications, 2016)
Mutual trust and relationship between doctors and patients is an important factor of treatment plan. Changing trends in medical field does affect this relationship. This article reviews the basic code of conduct for every medical practitioner.